Elmo saves Christmas [videorecording (DVD)] - Squires, Emily; Clash, Kevin; Spinney, Caroll; Mazzarino, Joseph (Genius Entertainment, 2008)
Can there be such a thing as too much Christmas? Elmo gets to see what the world would be like if every day were Christmas.